Quantum and semiclassical dynamical studies of nonadiabatic processes in solution: achievements and perspectives. Issue 14 (30th March 2021) - Santoro, Fabrizio; Green, James A.; Martinez-Fernandez, Lara; Cerezo, Javier; Improta, Roberto
Abstract : We concisely review the most used methodological approaches to model nonadiabatic dynamics in isotropic solutions and their applications. Abstract : We concisely review the main methodological approaches to model nonadiabatic dynamics in isotropic solutions and their applications. Three general classes of models are identified as the most used to include solvent effects in the simulations. The first model describes the solvent as a set of harmonic collective modes coupled to the solute degrees of freedom, and the second as a continuum, while the third explicitly includes solvent molecules in the calculations. The issues related to the use of these models in semiclassical and quantum dynamical simulations are discussed, as well as the main limitations and perspectives of each approach.